2018
DOI: 10.1530/ec-18-0039
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac magnetic resonance imaging of myocardial mass and fibrosis in primary aldosteronism

Abstract: BackgroundPrimary aldosteronism (PA) is associated with increased cardiovascular morbidity, presumably due to left ventricular (LV) hypertrophy and fibrosis. However, the degree of fibrosis has not been extensively studied. Cardiac magnetic resonance imaging (CMR) contrast enhancement and novel sensitive T1 mapping to estimate increased extracellular volume (ECV) are available to measure the extent of fibrosis.ObjectivesTo assess LV mass and fibrosis before and after treatment of PA using CMR with contrast enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 49 publications
2
17
0
1
Order By: Relevance
“…Myocardial fibrosis in PA also can be assessed by cardiac MRI with gadolinium-enhanced imaging or other imaging processing methods evaluating the texture of the myocardium. PA patients have been shown to have a higher fibrosis index, LV stiffness, and noninfarct-related fibrosis compared with healthy volunteers or EH controls, while only one small-sized study has reported conflicting data [82]. Although no difference was found in myocardial fibrosis after treatment in that study [82], it was limited by a small sample size.…”
Section: Clinical Studies Of Pa and Treatment Effects On Myocardial Fmentioning
confidence: 92%
See 1 more Smart Citation
“…Myocardial fibrosis in PA also can be assessed by cardiac MRI with gadolinium-enhanced imaging or other imaging processing methods evaluating the texture of the myocardium. PA patients have been shown to have a higher fibrosis index, LV stiffness, and noninfarct-related fibrosis compared with healthy volunteers or EH controls, while only one small-sized study has reported conflicting data [82]. Although no difference was found in myocardial fibrosis after treatment in that study [82], it was limited by a small sample size.…”
Section: Clinical Studies Of Pa and Treatment Effects On Myocardial Fmentioning
confidence: 92%
“…One recent study from Italy reported pathological findings from endomyocardial biopsies in PA patients, and revealed prominent myocardial hypertrophy and fibrosis, with reversible water accumulation in the cytosol and organelles of cardiomyocytes and microvascular smooth muscle cells after adrenalectomy [76]. However, the small sample size limited the clinical and statistical power with regards to proving an increase in myocardial fibrosis due to PA. Clinically, myocardial fibrosis in PA is mostly evaluated by echocardiography and cardiac MRI, in conjunction with serum biomarkers that are elevated during increased myocardial fibrosis, as listed in Table 1 [17,36,39,67,73,[76][77][78][79][80][81][82].…”
Section: Clinical Studies Of Pa and Treatment Effects On Myocardial Fmentioning
confidence: 99%
“…If the myocardial brosis increases in PA patients, the answer is still controversial [13][14][15][16]26]. Cardiac biopsy samples from four male PA patients exhibited 1.5-fold more brosis than those from EH patients (14% vs. 6%) [16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that cardiac dysfunction results from brosis of the myocardium in many diseases, such as heart failure [10], hypertrophic cardiomyopathy [11], and diabetic patients [12]. As to if myocardial brosis increases in PA patients, the answer is still controversial [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation